Compound K improves skin barrier function by increasing SPINK5 expression - Park, No-June; Bong, Sim-Kyu; Lee, Sullim; Jung, Yujung; Jegal, Hyun; Kim, Jinchul; Kim, Si-Kwan; Kim, Yong Kee; Kim, Su-Nam (KOREAN SOC GINSENG, 2020)
Background: The skin acts as a barrier to protect organisms against harmful exogenous agents. Compound K (CK) is an active metabolite of ginsenoside Rb1, Rb2 and Rc, and researchers have focused on its skin protective efficacy. In this study, we hypothesized that increased expression of the serine protease inhibitor Kazal type-5 (SPINK5) may improve skin barrier function. Methods: We screened several ginsenosides to increase SPINK5 gene promoter activity using a transactivation assay and found that CK can increase SPINK5 expression. To investigate the protective effect of CK on the skin barrier, RT-PCR and Western blotting were performed to investigate the expression levels of SPINK5, kallikrein 5 (KLK5), KLK7 and PAR2 in UVB-irradiated HaCaT cells. Measurement of transepidermal water loss (TEWL) and histological changes associated with the skin barrier were performed in a UVB-irradiated mouse model and a 1-chloro-2,4-dinitrobenzene (DNCB)-induced atopic dermatitis-like model. Results: CK treatment increased the expression of SPINK5 and decreased the expression of its downstream genes, such as KLKs and PAR2. In the UVB-irradiated mouse model and the DNCB-induced atopic dermatitis model, CK restored increased TEWL and decreased hydration and epidermal hyperplasia. In addition, CK normalized the reduced SPINK5 expression caused by UVB or DNCB, thereby restoring the expression of the proteins involved in desquamation to a level similar to normal. Conclusions: Our data showed that CK contributes to improving skin-barrier function in UVB-irradiated and DNCB-induced atopic dermatitis-like models through SPINK5. These results suggest that therapeutic attempts with CK might be useful in treating barrier-disrupted diseases. (C) 2019 The Korean Society of Ginseng. Publishing services by Elsevier B.V.
Keywords: SERINE-PROTEASE INHIBITOR; ATOPIC-DERMATITIS; NETHERTON-SYNDROME; STRATUM-CORNEUM; ULTRAVIOLET-B; GENE; ASSOCIATION; MUTATIONS; POLYMORPHISMS; DESQUAMATION